In-situ plasmonic tracking oxygen evolution reveals multistage oxygen diffusion and accumulating inhibition - Jun-Gang Wang (Nature Portfolio, 2021)
Understanding mass transfer processes concomitant with gas evolution reactions is important in energy research. Here, the authors show diffusion tracking of dissolved oxygen on copper nanostructured interface with plasmonic signal, and provide a direct observation of the interfacial mass transfer processes.